Human Lipoxygenase Pathway Gene Variation and Association with Markers of Subclinical Atherosclerosis in the Diabetes Heart Study - Freedman, Barry I.; Carr, J. Jeffrey; Hedrick, Catherine C.; Rich, Stephen S.; Burdon, Kathryn P.; Liu, Yongmei; Register, Thomas C.; Bowden, Donald W.; Rudock, Megan E.; Lehtinen, Allison B.; Langefeld, Carl D. (Mediators of Inflammation, 2010)
Aims. Genes of the 5-lipoxygenase pathway are compelling candidates for atherosclerosis. We hypothesize that polymorphisms in ALOX12, ALOX15, ALOX5, and ALOX5AP genes are associated with subclinical atherosclerosis in multiple vascular beds. Methods. Families with two or more siblings with type 2 diabetes and their nondiabetic siblings were studied as part of the Diabetes Heart Study (DHS). European American diabetic (n=828) and nondiabetic (n=170) siblings were genotyped for SNPs in the ALOX12, ALOX15, ALOX5, and ALOX5AP genes. Subclinical measures of atherosclerosis (IMT, coronary (CorCP), carotid (CarCP) and aortic (AorCP) calcified plaque) were obtained. Results. Associations were observed between ALOX12 with CorCP, ALOX5 with CorCP, AorCP, and IMT, and ALOX5AP with CorCP and CarCP, independent of known epidemiologic risk factors. Further, lipoxygenase pathway SNPs that were associated with measures of atherosclerosis were associated with markers of inflammation (CRP, ICAM-1) and calcification (MGP). Conclusions. Polymorphisms within ALOX12, ALOX5, and ALOX5AP are genetically associated with subclinical atherosclerosis and with biomarkers of disease in families with type 2 diabetes. These results suggest that variants in lipoxygenase pathway genes may have pleiotropic effects on multiple components that determine risk of cardiovascular disease.